Covid 19 Contexts Shaping Teaching Practice Discourses: University of Eswatini - Dlamini, Boyie S. (Advances in Social Sciences Research Journal, 2021)
Abstract This study examines how the Covid 19 Teaching practice contexts elicited the intended professional development principles among the PGCEs’ and BEDS’ four 2020 cohorts at the University of Eswatini. The pedagogical knowledge interaction scheme theoretical framework was used to unpack related concepts. The participants, 23 were sampled through purposive stratified sampling. The semi-semi structured questionnaires and classroom observations were used to collect data. Content analysis was used as a data collecting and analysing tool to analyse and describe the pedagogical discourses within the classroom and institutional contexts. The finding indicated that the mismatch subject arrangement undermined the production of specialised knowledge and alienated some students from their professional engagement and, stifled students’ capabilities to engage into self-reflection. Covid 19 pandemic created complex educational contexts in which incongruent messages related to the fundamental principles of teaching practices were communicated and reinforced. It is concluded that Covid 19 contexts presented a challenge of considerable complexity for the 2020 teaching practice and denied the Trainees the opportunity to learn from experienced teachers or mentors. It is recommended that Coordinators should embrace Covid 19 dynamics in their planning and implementation to protect the teaching practice principles. Key words: Covid 19 contexts, Teaching practice principles